2018
DOI: 10.1128/mbio.01192-18
|View full text |Cite
|
Sign up to set email alerts
|

The Main Role of Srs2 in DNA Repair Depends on Its Helicase Activity, Rather than on Its Interactions with PCNA or Rad51

Abstract: Homologous recombination (HR) is a mechanism that repairs a variety of DNA lesions. Under certain circumstances, however, HR can generate intermediates that can interfere with other cellular processes such as DNA transcription or replication. Cells have therefore developed pathways that abolish undesirable HR intermediates. The Saccharomyces cerevisiae yeast Srs2 helicase has a major role in one of these pathways. Srs2 also works during DNA replication and interacts with the clamp PCNA. The relative importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 103 publications
2
6
0
Order By: Relevance
“…Sequence analysis of Srs2 has found a putative BRC repeat (F**A motif) and mutation of the key phenylalanine to an alanine residue (F891A) results in complete disruption of Rad51 interaction, but no change in sensitivity to the DNA damaging agent Methyl methanesulfonate (MMS) or overall cell viability [126]. This observation is also supported by the finding that removing the Rad51-binding site in Srs2 results in no observable differences to cell viability (as measured by cell survival over time) or response to genotoxic stress [127,128].…”
Section: Srs2 Rtel1 and Helqmentioning
confidence: 88%
“…Sequence analysis of Srs2 has found a putative BRC repeat (F**A motif) and mutation of the key phenylalanine to an alanine residue (F891A) results in complete disruption of Rad51 interaction, but no change in sensitivity to the DNA damaging agent Methyl methanesulfonate (MMS) or overall cell viability [126]. This observation is also supported by the finding that removing the Rad51-binding site in Srs2 results in no observable differences to cell viability (as measured by cell survival over time) or response to genotoxic stress [127,128].…”
Section: Srs2 Rtel1 and Helqmentioning
confidence: 88%
“…The apparent discrepancy between the in vivo and in vitro roles of the Srs2–Rad51 interaction may be because in vivo there are other factors, such as PCNA, that are equally, if not more, important for the recruitment of Srs2 for Rad51 filament disruption. In fact, a recent genetic study on SRS2 concluded that the main role of Srs2 in DNA repair depends on its helicase/translocase activity instead of its Rad51or PCNA interaction (Bronstein et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the inhibition of repair by Srs2 is not likely to be by Rad51 eviction, since OE of Rad51, in contrast to that of Rad52, has no suppression effect. Instead, we assume that Srs2 directly inhibits, or counteracts, the activity of Rad52 (21,22). In support of this idea, a physical interaction was characterized between Srs2 and Rad52 (47).…”
Section: Overexpression Of Rad52 or Of Elg1 Allows Increased Damage Tmentioning
confidence: 91%
“…PCNA SUMOylation at K164 seems to be evolutionarily conserved and has been observed also in other organisms (17,18). SUMOylation of PCNA can lead to the recruitment of Srs2, a UvrD-like helicase that can disrupt Rad51 presynaptic filaments and thus prevent homologous recombination (HR) (19)(20)(21)(22)(23). Functional homologs of Srs2 seem to exist in other organisms (e.g., PARI [18] and RTEL1 [24]).…”
mentioning
confidence: 95%